Strategi Pengembangan Bisnis Bawang Goreng UD. HJ. MBOK SRI Di Kota Palu, Sulawesi Tengah - Nur T., Fanny Iswarini; M. Baga, Lukman; Burhanuddin, Burhanuddin (Jurnal Agribisnis Indonesia, 2022)
Domestic shallot production generally has met domestic needs. Agricultural development aims to increase the production and income of farmers, especially in Central Sulawesi. One of the mainstay commodities that are expected to increase farmers' income is the local Palu shallot commodity. The purpose of this research is mapping the current business model of UD. Hj. Mbok Sri, analyzing the internal and external conditions of the business and formulating a design for improving its business model. The methods that used in this research are the Business Model Canvas (BMC), SWOT and Blue Ocean Strategy (BOS). This research was conducted by mapping the latest business models based on the 9 elements that exist in BMC, then it will be followed by a SWOT analysis on each BMC element and determining the strategy to overcome the problems that was existing at UD. Hj. Mbok Sri. Then it will be combined for improving the new business model from UD. Hj. Mbok Sri by using Blue Ocean Strategy’s perspective. The results showed that the alternative strategies that could be pursued in the development of UD. Hj. Mbok Sri can be focussed on customer segments elements, value propositions, channels, customer relationships and key partnerships, namely by optimizing the use of social networks, adding new customer segments and increasing the value proposition. These will have effects on better established customer and partnership relationships. Key activities will run smoothly and the main resources will also be more adequate, so that the flow of income will increase and the cost structure can be managed properly.